DRYING OF POTATO SLICES: EFFECT OF PRETREATMENTS AND MATHEMATICAL MODELING - Doymaz, Ibrahim (WILEY, 2012)
The effect of pretreatments on drying characteristics of potato slices was investigated in a cabinet dryer. The experiments were conducted on potato slices with thickness of 8 mm at 65C with an air velocity of 2.0 m/s. Prior to drying, potato slices were pretreated with citric acid solution (1:25 w/w, 3 min, 20C) or blanched hot water (3 min, 80C). Besides, the untreated samples were dried as control. The shortest drying time was obtained with potatoes pretreated with citric acid solution. The drying data were fitted with ten mathematical models available in the literature. The results indicated that Midilli et al., modified Henderson and Pabis, Verma et al., two-term, parabolic and logarithmic models were found the better to describe the drying of potato slices. The values of effective moisture diffusivity were found to be range between 1.78 x 10-10 and 2.94 x 10-10 m2/s and influenced by pretreatments. PRACTICAL APPLICATIONS The pretreatment followed by air-drying may provide a practical method for the preservation of fruits and vegetables. The experimental study evaluates the pretreatment and drying conditions of potato slices. The objective of this study was to study the effect of pretreatments on the drying times and rehydration ratios, to fit the experimental data to 10 thin-layer drying models available in the literature, and to compute effective moisture diffusivity of samples. This research is useful for producers of dry potatoes.
Keywords: REHYDRATION KINETICS; MOISTURE DIFFUSIVITY; LAYER; DEHYDRATION; TEMPERATURE; SELECTION; BEHAVIOR; QUALITY; WHITE; L.; Food Science & Technology